Advances in Diagnosis of Respiratory Virus Infections - Loeffelholz, Michael; Chonmaitree, Tasnee (International Journal of Microbiology, 2010)
The diagnosis of respiratory virus infections has evolved substantially in recent years, with the emergence of new pathogens and the development of novel detection methods. While recent advances have improved the sensitivity and turn-around time of diagnostic tests for respiratory viruses, they have also raised important issues such as cost, and the clinical significance of detecting multiple viruses in a single specimen by molecular methods. This article reviews recent advances in specimen collection and detection methods for diagnosis of respiratory virus infections, and discusses the performance characteristics and limitations of these methods.